PENGARUH PRAKTIK PEMBUKUAN DAN PENGETAHUAN AKUNTANSI TERHADAP KINERJA KEUANGAN DENGAN KETERAMPILAN AKUNTANSI PEMILIK SEBAGAI VARIABEL MODERASI - Hamzah, Amir; Rochmanisari, Fitria; Andini, Anita Putri; Ningrum, Malinda (Jurnal Riset Keuangan dan Akuntansi, 2024)
This study aims to analyze the impact of bookkeeping practices and accounting knowledge on financial performance with the owner's accounting skills as a moderating variable, using a case study on SMEs in Kuningan Regency. This research adopts descriptive and verificative methods. The subjects of this study are SMEs in Kuningan Regency, employing random sampling techniques, with a sample size of 154 SMEs. The data source used is primary data, obtained directly from respondents through questionnaires measured using a Likert scale. Data analysis techniques are performed using Structural Equation Modelling (SEM) based on Partial Least Squares (PLS).The results of the study indicate that: (1) Bookkeeping practices do not have a significant impact on financial performance; (2) Accounting knowledge has a significant impact on financial performance; (3) The owner's accounting skills also have a significant impact on financial performance; (4) The owner's accounting skills do not moderate the impact of bookkeeping practices on financial performance; and (5) The owner's accounting skills moderate the impact of accounting knowledge on financial performance. These results provide important insights for SMEs in improving their financial performance through enhancing accounting knowledge and skills. Keywords: Bookkeeping Practices, Accounting Knowledge, Owner's Accounting Skills, Financial Performance, SMEs